Poznavanje in poistovetenje z identiteto znamke I feel Slovenia - Malovrh, Metka (Naše gospodarstvo, 2011)
Strong country brands are those that are well perceived by their target groups. However, strong brands are based on clear strategies, which are developed and managed by internal stakeholders of the country. The brand I feel Slovenia was born at the end of 2007. In the process of brand development, the views of internal stakeholders were considered. The brand is well recognized and perceived among the Slovenian public. Familiarity with the brand is due primarily to its visual elements (logo and slogan). In the article we present the results of two qualitative studies which suggest that identity elements are known only to the professional public (in our case brand implementers or opinion leaders in key areas of the country), but not to the people of Slovenia. In addition, the results suggest that Slovenians could identify themselves with the brand identity if they would have been introduced to the appropriate content.
Keywords: blagovne znamke; država; state; identiteta; Slovenia; Slovenija